Continuous-flow left ventricular assist device treatment for arrhythmogenic right ventricular cardiomyopathy complicated by advanced biventricular failure – University of Tokyo experiences - Ono, Minoru (Frontiers in Cardiovascular Medicine, 2022)
Arrhythmogenic right ventricular cardiomyopathy (ARVC) is an inherited cardiomyocyte disease characterized by intractable ventricular arrhythmia in the majority of affected patients. Some of these patients also manifest right ventricular dysfunction and heart failure symptoms. Fatal ventricular arrhythmia has been the primary cause of death in ARVC patients. However, increased early recognition of ARVC and improvement in arrhythmic risk stratification and treatment have dramatically improved survival. A small proportion of the patients are further complicated by left ventricular impairment at the late phase in addition to right heart failure, for whom only heart transplantation is the last resort. Because of the relative rarity of ARVC with biventricular failure, no consensus or guideline has been reported on how to effectively support these patients with a mechanical circulatory device. Herein, four ARVC patients with biventricular failure were presented who were successfully bridged to heart transplantation after long-term support by isolated continuous-flow LVAD.